Peranan Sektor Pertanian dalam Perencanaan Pembangunan Ekonomi - Indra Hartini; Iskandar Malian; Emila Sholiha (IPM2KPE, 2023)
The aim of the research is to facilitate local governments in planning and making development policies for sub-districts in Lahat Regency so that they will be able to maintain and increase the role of the agricultural sector in the regional economy. This research method is descriptive quantitative. Qualitatively, it is an explanation or verbal descriptions. While quantitative is a descriptive discussion using the formula of financial ratios. The results of calculating the average total income earned by lowland rice farmers per production period (4 months) is IDR 2,974,062.13 per hectare, so the amount of income for lowland rice farmers each month is IDR 743,515.53. The results of calculating economic profitability or return assed (ROA) is an average of 75.80% for each hectare once harvested. The conclusions in this study are, a) the income level of rice farmers in Kota Agung District, Lahat Regency is not feasible based on the minimum wage (UMR) in Lahat Regency. Thus the hypothesis proposed can be accepted; b) the ability of paddy rice farmers in Kota Agung District, Lahat Regency to benefit from farming through all available capabilities and resources, shows a very good condition so that the resulting farming results can be appropriate according to the wishes of the farmers. Keywords: Agricultural Sector in Development Planning